13C-sodium acetate breath test for evaluation of gastric emptying times in dogs with gastric dilatation-volvulus - Schmitz, S.; Jansen, N.; Failing, K.; Neiger, R. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2013)
Objective: The aim of the study was to assess solid phase gastric emptying via non-invasive 13C-sodium acetate breath test in large breed dogs with or without gastric dilatation-volvulus (GDV). Material and methods: Dogs were recruited into one of the following groups: group 1 = healthy large breed dogs with no history of GDV, group 2 = dogs that underwent elective abdominal surgery for reasons unrelated to the gastrointestinal tract, and group 3 = dogs that underwent laparotomy and gastropexy to correct GDV. The dogs were fed a test meal containing 100 mg 13C-sodium acetate (for group 2 and 3, this was < 48 hours post-operatively). Breath samples were obtained at baseline and every 30 minutes for 3 hours, then every hour for a total of 7 hours. 12CO2/13CO2 ratio was measured for each breath sample via non-dispersive infrared spectroscopy and 25%, 50% and 75% gastric emptying times were calculated and compared between groups. Results: Gastric emptying times were significantly prolonged in dogs undergoing surgery (group 2) compared to group 1 and 3. Also, gastric emptying times of dogs with GDV were significantly prolonged compared to controls, but not to the same extent as dogs in group 2. Conclusion and clinical significance: There was a significant effect of abdominal surgery on gastric emptying times. Surprisingly, dogs after GDV surgery and gastropexy had shorter gastric emptying times than dogs undergoing laparotomy for reasons other than GDV, but still prolonged compared to healthy controls. The reason for these differences requires further study.
Keywords: Canine; gastric stasis; motility; non-dispersive infrared spectroscopy; stomach